P1441 Predictors of systemic embolisms in a large cohort of left ventricular noncompaction patients. (17th January 2020) - Casas, G; Oristrell, G; Limeres, J; Barriales, R; Gimeno, J R; Garcia Pavia, P; Zorio, E; Villacorta, E; Jimenez Jaimez, J; Bayes, A; Garcia Pinilla, J M; Palomino, A J; et al.
Abstract: BACKGROUND Left ventricular noncompaction (LVNC) is associated with an increased risk of systemic embolisms (SE). However, incidence and risk factors are not well established. PURPOSE To evaluate the rate of SE in LVNC and describe risk factors. METHODS LNVC patients were included in a multicentric registry. Those with SE were considered for the analysis. RESULTS 514 patients with LVNC from 10 Spanish centres were recruited from 2000 to 2018. During a median follow-up of 4.2 years (IQR 1.9-7.1), 23 patients (4.5%) had a SE. Patients with SE (Table 1) were older at diagnosis, with no differences in gender and had similar cardiovascular risk factors. They were more frequently under oral anticoagulation (OAC). Besides, they had a more reduced LVEF, and more dilated LV and left atrium (LA). Late gadolinium enhancement (LGE) was more frequent, altogether suggesting a more severe phenotype. Patients with SE had non-significantly higher rates of hospitalization for heart failure (33% Vs 24%, p = 0.31) and atrial fibrillation (35% Vs 19%, p = 0.10). In multivariate analysis, only LA diameter was an independent predictor of SE (OR 1.04, p = 0.04). A LA diameter > 45 mm had an independent 3 fold increased risk of SE (OR 3.04, p = 0.02) (Image 1). CONCLUSIONS LVNC carries a moderate mid-term risk of SE, which appears to be irrespective of atrial fibrillation and associated with age, LV dilatation and systolic dysfunction and mainly LA dilatation. This subgroup of patients should be considered for oral anticoagulation in primary prevention.